Qualidade nutricional de biscoitos integrais comercializados em um município da fronteira oeste do RS - (:unkn) unknown (Universidade Federal do Pampa, 2022)
Many consumers seek healthier products, including biscuits. The aim of this study was to verify the nutritional quality of industrialized wholemeal biscuits. Data collection was carried out in 3 supermarket and 3 natural products stores in Itaqui, Brazil. Data were collected in loco, through written and/or photografic records of the ingredientes list and the nutritional information table, presentend on the product labels. Biscuits were classified according to the NOVA classification and the nutrientes evaluated according to the labeling legislation.74 biscuits were analyzed, being 78% sweet (n=58) and 22% salty (n=16). Most of them (95%) were classified as ultraprocessed food and the average of ingredientes was 16,36, being higher (p<0,05) on sweet biscuits. The most frequent ingrediente category was in natura and minimally processed foods (38,08%), followed by food aditives (29,7%) and culinary ingredientes (21,33%). When avaliated regarding nutrientes, it was observed that the biscuits were formed mainly by carbohydrates (60,48%) and fats (15,34%) and had not higher fiber content (average of 1,99g of fiber for portion). Sweet biscuits had higer values of sugars (p<0,05) and total fat, and salty biscuits had higher values (p<0,05) of sodium. Vegetal fat was more frequent in sweet biscuits (p<0,05). This study demonstrated that whole biscuits have low nutritional quality, especially sweet biscuits.
Nutritional quality of whole-grain biscuits sold in a municipality on the western border of RS
Keywords: Produtos naturais; Supermercados; Biscoitos; Rotulagem de alimentos; Valor nutritivo; Natural products; Supermarkets; Cookies; Food labeling; Nutritive value; CIENCIAS DA SAUDE